An integrated type of MIG torch cleaner - Mohd Saffririzal, Abdul Halim (2012)
This thesis deals with the designing and development of MIG weld torch cleaner that efficient and effective clean in order to protect the torch from corroded during the cleaning process. The objectives of this thesis are to develop a torch cleaner that can clear and retards buildup of spatter in welding torch. The purpose for this study is to maintain quality in your MIG welding cell by removing spatter build-up in the nozzle. The scope of this project is that the validation of the torch cleaner through analysis software is considered precise. The design will justify the ergonomics principle and the finite element analysis was performed. The finite element model of design was analyzed using Static Stress with Linear Material Models. Three designs of torch cleaner were constructed. For the reamer blade, the analysis of strength of material is used in for the construction. For the each component of MIG torch cleaner, the analysis of different forces had been applied. The forces that being applied shown that the ability of the torch cleaner to support the force. The result shows that the design A has lower Stress von Misses than design B and design C. From the result, it is observed that the design is success and achieved to produce the special tool without using any power sources. An analysis of this product is achieved with comparing the three designs. The design A has meets all the criteria and specification that needed in this project. Lastly, the result of the testing and fabrication is overall succeeding in order to protect the torch from corroded during the cleaning process at the same time meets with the entire objective in this project.